Microcavities accompanying a zigzag line in friction stir welded A6082-T6 alloy joint. (January 2015) - Dai, Q. L.; Wang, X. Y.; Hou, Z. G.; Wu, J. J.; Shi, Q. Y.
<x content-type="archive" xml:space="preserve">Abstract</x> An Al–Mg–Si alloy was friction stir welded (FSW), and the microstructure of the zigzag line in the welds was investigated using optical microscopy, energy dispersive X-ray spectroscopy and scanning electron microscopy. The effect of the zigzag line on the mechanical properties of the as welded joints was also examined. It was found that in the welds with high heat input, small discontinuous cavities or microcracks of several micrometres in size exist along the zigzag line, and the microcracked zigzag line was found to significantly affect the face bend properties of the FSW joint, but had limited influence on the tensile properties of the butt welds. In joints with low heat input, the zigzag line was only composed of oxide particles, no cavities or microcracks were detected at the zigzag line.